math
posted by kat .
[2x(5x+2)]=2+(2x+7) help me please, i need step by step so that I won't get lost

math 
Ms. Sue
[2x(5x+2)]=2+(2x+7)
3x + 2 = 9 + 2x
3x  2x = 9  2
x = 7
Check:
14 + 35 + 2 = 9 + 14
23 = 23 
math 
Reiny
work the inner brackets first
[2x(5x+2)]=2+(2x+7)
2[2x  5x 2] = 2 + 2x + 7
2[3x  2] = 9 + 2x
6x + 4 = 9 + 2x
6x  2x = 9  4
4x = 5
x = 5/4 
go with Ms Sue's, scrap mine math 
Reiny
should have put my glasses on !
Respond to this Question
Similar Questions

Algebra
How do I solve for the elimination method: 5x + 3y= 7 and 7x  2y =13 (step 1); 10x + 6y =14 and 21x 6y = 39 ( step 2), 31x/31= 25/31, x= 25/31 (step 4). But after that I get lost. Can somebody help me out please. 
Algebra help
f(x)=x^34x^2x+4 How do I find the xintercept for this? 
math
please  How do we manually calculate the Present Value of annuity step by step using this formula: PV=R[1(1+i)n / i for example: PV = 2700[1(1+.065)4 ___________________ = 9249.66 0.065 How did they get this answer (9249.66)? 
Trigonometry
I need help proving the following identity: 4(sin^6(x)+cos^6(x)) = 43sin^2(2x) I am completely lost, if anybody can please give me a stepbystep guide to figuring this out, I would be forever grateful!! 
Physics
Can someone please show me step by step how to normalize e^5x in the interval (0, infinity)? 
chem
ok my professor lost me when explaining this material so please bare with me and help me step by step one of the questions is: after absorbing 1850J of energy as heat, the temperature of a .500kg block of copper is 37C what was its … 
ALGEBRA HELP
When solving the equation, what property was used to go from step 3 to step 4? 
Quick math help
In which step below does a mistake first appear in simplifying the expression? 
math
Help please select the approcimate values of x that are solutions to f(x)=0 where f(x)=5x^2+8x+5 I so am lost please show me step by step 
Math
I need help solving the problem not the answer. (Multiple Choice) The steps below show the incomplete solution to find the value of x for the equation 7x + 8 − 3x = −6 + 10: Step 1: 7x + 8 − 3x = −6 + 10 Step 2: 7x + 8 − …